André Scrima, Reader of Heidegger: From the Desert of Being to the Desert of the Monastery - Dancă, Mihai-Iulian (Review of ecumenical studies, 2020)
Little is known about the meeting which took place between Martin Heidegger and André Scrima. Aside from unfolding within the master-disciple framework, it is a witness above all of a fruitful dialogue between western philosophy and eastern theology about a common concern: the desert as the unfolding of our being in the world. It is this concern, the guiding light in fact for this article, which will develop here in several stages: First, by unravelling the hostile meanings of the word "desert." Second, by using it as a reading key to explore the foundations of contemporary civilization and especially by analysing it as a concept for a new topography of Being. The final stage will tackle the foundational link which unites the desert and monastic life. It is this connection which will finally allow us to understand how the love of God, which pushes the monk into the desert, can be so decisive for a new understanding of Being.